Prevalence, Fate and Effects of Plastic in Freshwater Environments - Khan, Farhan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Plastic (and microplastic) pollution has been described as one of the greatest environmental challenges of our time, and a hallmark of the human-driven epoch known as the Anthropocene. It has gained the attention of the general public, governments, and environmental scientists worldwide. To date, the main focus has been on plastics in the marine environment, but interest in the presence and effects of plastics in freshwaters has increased in the recent years. The occurrence of plastics within inland lakes and rivers, as well as their biota, has been demonstrated. Experiments with freshwater organisms have started to explore the direct and indirect effects resulting from plastic exposure. There is a clear need for further research, and a dedicated space for its dissemination. This book is devoted to highlighting current research from around the world on the prevalence, fate, and effects of plastic in freshwater environments.